Pengaruh Pemberian Susu Afkir terhadap Konsumsi Pakan, Pertambahan Bobot Badan Harian dan Konversi Pakan Broiler - Muhammad Angsori; Novi Eka Wati; Kunaifi Wicaksana (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The objective of this experiment was to determine the effect of rejecting milk on drinking water on feed intake, daily body weight gain and feed conversion of broilers. The material of this study included 200 broilers aged 14 days given P0= drinking water treatment without giving an reject milk and P1= drinking water with the addition of rejected milk. Chickens were treated for 14 days and fed with PK= 22.0-23.0%, Fat= 5.0%, Calcium= 0.9%, Phospor= 0.6%, ME= 3050-3150 Kcal/Kg. In conclusion, rejected milk in drinking water has a significant effect on daily body weight gain, but does not significantly effect on feed intake and feed conversion. The daily body weight gain of P1 was higher than P0. Keywords: broilers, daily weight gain, feed intake, feed conversion ratio, rejected dairy milk